VENDIAN FORELAND BASIN OF THE SIBERIAN CRATONIC MARGIN: PALEOPANGEAN ACCRETIONARY PHASES - Sovetov J.K. (My University, 2002)
Vendian, chiefly clastic sedimentation on the southwest of the Siberian craton is discussed under the tenet of a foreland basin that came into being in the Vendian epoch at the margin of the Siberian continent (craton) due to its collision with island arcs and microcontinents. The Vendian foreland basin of the Siberian cratonic margin, over 3000 km in length, was formed in the Early and Late Vendian. To use a paleotectonic framework, the terrestrial and marine deposition in point took place in the Yenisei-Baikal belt of foredeeps and in its coeval Baikit-Nepa belt of forebulges in the cratonic interior. Vendian age of molasse and the foreland basin is proved by new data: (1) tillites reported from the base of the Oselkovaya Group (Marnya Formation) of the Sayan foredeep and (2) the find of a Metazoa mollusk biota. The tillite-bearing horizon occurs at the base of the "lower marine assemblage" and, using cyclic sequences and carbonate sedimentary marker systems, it is traceable on the Yenisei Ridge, in Cisbaikalia, and in the cratonic interior. Sedimentologic data and the vector of clastic transport suggest that the ice cap was located on the Siberian craton, and the Siberian glacial horizon is correlatable to the global Laplandian horizon of the Vendian [Chumakov, 1978]. The foreland basin passed three evolutionary phases: (1) initial accretionary, (2) glacial (pre-collisional), and (3) collisional. Based on sedimentologic data, each phase falls into several evolutionary stages, each stage reflecting an erosion pulse and redeposition of clastic sediments. During the accretionary and collisional phases, changes in sedimentary systems were associated with tectonic activity and, indirectly, with eustatic sea-level oscillations. During the glacial phase, deposition of third-order cyclic sequences was chiefly controlled by eustatic changes of the sea-level, forced by growth and melting of ice caps. The synchroneity and interplay of climatic and tectonic events in the Vendian on most continents and microcontinents can be explained by a model for the Paleopangean supercontinent accretion in the Vendian.
Keywords: VENDIAN FORELAND BASIN; ACCRETIONARY PHASES; SEDIMENTATION; SIBERIAN CRATON; Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский